The end of everything [compact disc, unabridged] : a novel - Abbott, Megan., 1971- (Blackstone Audio, Inc., 2011)
Thirteen-year-old Lizzie Hood and her neighbor Evie Verver are best friends. Lizzie believes her neighbor's family is idyllic and loves spending time over there. But when Evie disappears, Lizzie is beset with questions about her friends whereabouts. As she begins her own quest for the truth, Lizzie uncovers a series of secrets that makes her question everything she knew about Evie.